STRATEGI BUMDES DALAM MENINGKATKAN PENGHASILAN UNIT USAHA DI DESA SIDOMOJO KECAMATAN KRIAN KABUPATEN SIDOARJO - Churil Fauziah; Isnaini Rodiyah (Journal Publicuho, 2025)
This study aims to analyse the strategy of the Makmur Jaya Village-Owned Enterprise (BUMDes) in increasing the income of business units, especially in the Integrated Waste Management Facility (TPST 3R) in Sidomojo Village, Krian District, Sidoarjo Regency. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. Data analysis uses the Miles and Huberman interactive model. This study uses strategy indicators from Koteen's theory, namely Organisational Strategy, Resource Strategy, and Program Strategy. The results of the study show that although TPST 3R has the highest turnover contribution (74.85% of total BUMDes income), various obstacles are still faced, such as weak coordination, lack of human resources, minimal budget, and suboptimal internal and external communication. The potential for developing a maggot cultivation program as an alternative to increasing income is very large, but is hampered by inadequate infrastructure. Therefore, the strategy to increase BUMDes Makmur Jaya's income needs to be focused on improving management, strengthening human resources, developing cooperation, and optimising superior programs based on local potential.